ENT300 Business Model Canvas For Tiffin Carrier Lunch Delivery / Nurul Aida Athirah Shaik Abdul Rani - Shaik Abdul Rani, Nurul Aida Athirah (2020)
Tiffin is established in Asia during the British colonial era in the late 18th century. The word tiffin was coined to mean any culinary indulgence within the day typically between breakfast and dinner. Today, tiffin means a packed lunch box, afternoon tea, a savory snack, or sweet meal. The tiffin culture widespread throughout Asia and was popular until the 60s. The tiffin is known by many names in many cultures. For example: mangkuk tingkat (Malay), rantang (Indonesia), safartas (Arab), dabba (India). The tiffin ranges from the simple 2 tiers to the more elaborate 4 tiers. Previously, tiffin carriers were the first thing that came to mind when thinking of transporting and storing foods. Over time, there is decline in the use of tiffin carriers due to the onset of more and more restaurants, fast foods chains and with the advancement of food packaging. However, the fast packaging leaves a damaging trail of destruction to our environment. Due to this, I would like to retrieve back the use of tiffin carriers as packaging of foods. The idea of my business is to prepare meals, packed it in tiffin carriers and deliver it freshly to my customers. Using the contemporary tiffin carriers of today, which the form and overall shapes are attractive and designed to ensure easy cleaning and maintenance. Primarily made of stainless steel, it is manufactured to comply with food grade standards and ensured that it is safe and hygienic.